Proceedings of the 2015 Chinese Intelligent Systems Conference Volume 1 - Jia, Yingmin; Du, Junping; Li, Hongbo; Zhang, Weicun (Lecture Notes in Electrical Engineering, 2016)
This book presents selected research papers from the 2015 Chinese Intelligent Systems Conference (CISC'15), held in Yangzhou, China. The topics covered include multi-agent systems, evolutionary computation, artificial intelligence, complex systems, computation intelligence and soft computing, intelligent control, advanced control technology, robotics and applications, intelligent information processing, iterative learning control, and machine learning. Engineers and researchers from academia, industry and the government can gain valuable insights into solutions combining ideas from multiple disciplines in the field of intelligent systems.